(untitled) (Preventif : Jurnal Kesehatan Masyarakat, 2024)
Purpose: This study aims to examine the influence of oral health literacy and oral health care behavior of stunted toddlers. Methods: observational study with a case control approach. The population includes 3 sub-districts in Palaran District which is one of the loci for handling stunting in Samarinda City. The number of samples in this study was 90 cases: 180 controls with a total of 270 respondents, mothers of toddlers. Variables are oral health literacy, social demographics, oral health care parenting patterns. , and def-t index. The instrument used was Health Literacy Dentistry-Indonesian Version (HeLD-ID). Data were analyzed using the crossectional test Result: The results showed that the largest proportion of childhood caries is found in stunted children (27.8%). There are differences in the level of maternal education and the incidence of stunting between the case and control groups. (p value= 0.019). Interventions are needed that integrate oral health literacy education with improving nutritional intake, especially for stunted toddlers.